The mechanical characteristic of rock salt under uniaxial compression with low temperature effect - Jie Chen; Xilinx Shi; Jiankun Zhou (Functional Materials, 2016)
he mechanical characteristic of rock salt under uniaxial compression after effected by temperature was studied. The test temperature were 35, 50, 70°C. The results shown that: the Stress-strain curve of rock salt effected with low temperature under uniaxial compression process are similar, Which illustrated that the mechanical behavior of the salt rock specimen with room temperature can reflect the characteristics rock salt of rock salt underground. It is means that rock salt under the condition of short-term temperature drying effect, its mechanical characteristics was unchanged. Generally rock salt effected by temperature in the process of uniaxial compression, its acoustic emission ringing shown the similar property. The uniaxial mechanical properties was similar, when the rock salt specimens effected with temperature from 35 to 70°C.